Avaliação do nível de implantação da construção enxuta em três pequenas construtoras do Ceará - Santos, Éden Malveira dos (2020)
The application of the Lean Construction philosophy emerges as a potential tool to improve the traditional process of the construction industry, unleashing a series of clear benefits in the management process within civil construction. Knowing the need to improve techniques in construction processes and management in small construction companies, the objective of this work is to apply and evaluate the tool developed by Comelli (2017) for the context of small construction companies in Ceará. The methodological process took place by using questionnaires to the managers and engineers of the selected construction companies to identify qualitatively and quantitatively events about the lean philosophy applied to the construction sector. One of the contributions of the present work was a new division of the implantation levels, previously characterized by Comelli (2017). The protocol application showed that there is a certain degree of knowledge, interest, and beginning of the use of lean construction tools on the part of small construction companies. However, small companies in the construction sector still need to fully immerse themselves in the basic concepts of this philosophy and thus leverage better results in the production and management processes.